Batasan Perlindungan Hukum Perseroan Terbatas dalam Perspektif Piercing the Corporate Veil: (Analisis Putusan Pengadilan No. 47/Pdt.G/2021/PN. Mtr) - Akmal Budi Darmawan (CV Rewang Rencang, 2025)
A Limited Liability Company (PT) as a legal entity obtains legal protection through the principles of separate legal entity and limited liability, which limit the responsibilities of shareholders and management to the amount of capital contributed. However, in practice, these principles may be disregarded under the piercing the corporate veil doctrine when the legal entity is misused for personal gain. This study aims to analyze the limits of legal protection for PT through a case study of Decision No. 47/Pdt.G/2021/PN.Mtr, where the plaintiff sought to impose personal liability on the directors and commissioners of PT Amanah Group International (PT AGI) for the company's breach of contract. The research uses a normative juridical method with a statutory and case law approach. The findings show that although the piercing the corporate veil doctrine is accommodated in Article 3 paragraph (2) of the Indonesian Company Law (UUPT), the court in this case did not assign liability to PT AGI's management or shareholders. This is because the breach of contract was deemed to arise solely from the legal relationship between PT AGI and the plaintiff, and therefore legal responsibility could not be extended to other parties outside that contractual relationship. These findings reaffirm that the application of the piercing the corporate veil doctrine in Indonesian judicial practice still requires strict scrutiny and clear legal connections between the parties to be held liable.